Campus Canopy, 1935-02-13 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1935)
Turnbull, Ambos Head SGA -- Service Held for Dr. J.M. Pound -- Dies at Home in Athens Georgia -- History of Art Lectures -- Reverend Meeks Addresses Chapel -- How we Concentrate -- Dr. Punke Attends Education Meeting
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals